Enhancing Dye‐Triplet‐Sensitized Upconversion Emission Through the Heavy‐Atom Effect in CsLu2F7:Yb/Er Nanoprobes. (23rd November 2021) - Zhang, Peng; Ke, Jianxi; Tu, Datao; Li, Jiayao; Pei, Yifan; Wang, Le; Shang, Xiaoying; Guan, Tianyong; Lu, Shan; Chen, Zhuo; Chen, Xueyuan
Abstract: Lanthanide (Ln 3+ )‐doped upconversion (UC) nanoprobes, which have drawn extensive attention for various bioapplications, usually suffer from small absorption cross‐sections and weak luminescence intensity of Ln 3+ ions. Herein, we report the controlled synthesis of a new class of Ln 3+ ‐doped UC nanoprobes based on CsLu2 F7 :Yb/Er nanocrystals (NCs), which can effectively increase the intersystem crossing (ISC) efficiency from singlet excited state to triplet excited state of IR808 up to 99.3 % through the heavy atom effect. By virtue of the efficient triplet sensitization of IR808, the optimal UC luminescence (UCL) intensity of IR808‐modified CsLu2 F7 :Yb/Er NCs is enhanced by 1309 times upon excitation at 808 nm. Benefiting from the intense dye‐triplet‐sensitized UCL, the nanoprobes are demonstrated for sensitive assay of extracellular and intracellular hypochlorite with an 808‐nm/980‐nm dual excited ratiometric strategy. Abstract : A new class of upconversion (UC) nanocrystals of CsLu2 F7 :Yb/Er are developed to achieve efficient UC through triplet sensitization of NIR dye IR808, resulting in a 1309‐fold enhancement in UC luminescence intensity and a more than 180‐fold improvement of the absolute UC quantum yield over bare counterparts. Sensitive detection of intracellular ClO − is demonstrated by virtue of the 808‐nm/980‐nm dual excited ratiometric UC luminescence.